Implementing a smart data platform : how enterprises survive in the era of smart data - Lin, Yifei; Xiao, Wenfeng (O'Reilly Media, 2017)
With the big data boom, the rise of the Internet of Things (IoT), and the development of artificial intelligence (AI) applications, we've entered a new era of smart data. Unfortunately, not many enterprises are ready for it. Some companies are deficient in data management, while others lack standard data engineering systems. Some simply lag behind in data science. The bottom line is that many enterprises have no advanced technical platform for building IoT-driven AI applications. But there is a practical solution. This report examines how the Smart Data Platform, or SmartDP, enables enterprises to enhance their capacities in data management, data engineering, and data science. Authors Yifei Lin and Xiao Wenfeng of TalkingData describe a complete SmartDP solution that involves data, platform products, data applications, and consulting services--components that together can supplement and strengthen your current data platforms. Explore SmartDP from concept to practice and discover how implementing this solution will allow your organization to achieve new business value.